annual editions social problems - kurt finshterbusch (mcgraw-hill/dushkin, 2006)
social problems 05/06 is one in a series of over seventy-five volumes, each designed to provide convenient, inexpensive access to a wide range of current, carefully selected articels from some of the most respected magazine, newspers, and jurnals published today